PENINGKATAN EKSPOSUR DIGITAL UMKM DESA WRINGINSONGO KABUPATEN MALANG MELALUI PERANCANGAN KATALOG DIGITAL - Ade Ismail; Vipkas Al Hadid Fiardaus; Luqman Affandi; M. Hasyim Hasyim Ratsanjani; Wilda Imama Sabilla (P3M Politeknik Negeri Malang, 2026)
This community service program aimed to enhance the digital exposure of small and medium enterprises (UMKM) in Wringinsongo Village through the development of a digital catalog. The program involved analyzing the unique characteristics and market potential of local products, followed by collaboration with UMKM to create high-quality promotional materials. Key methods included digital marketing training, catalog development, and professional enhancements of promotional materials. The results showed significant improvements in product visibility through online platforms and enhanced UMKM knowledge of digital marketing strategies. Additionally, the quality of product promotion materials, including product descriptions, pricing, and high-quality images, was notably increased, leading to broader market reach and improved consumer engagement.